Modeling the Impact of Massive Open Online Courses (MOOC) Implementation Factors on Continuance Intention of Students: PLS-SEM Approach - Al-Mekhlafi, A.-B.A. (MDPI, 2022)
The Engineers in Society (EIS) course is a common course unique to Universiti Teknologi PETRONAS. However, every semester, the course receives 300 to 500 students, making managing and delivering it a challenging task. The EIS course is thus in need of a suitable mode of delivery where the teaching and learning process can cater to a large number of participants from a variety of programs. The aim of this study is to address the effect of Massive Open Online Courses MOOC factors implementation on the continuance intention of students. The study employed a survey that was designed from a literature review. The survey adopted a series of questions to gather information about the problem under investigation. One hundred forty-eight responses were collected from the students in different engineering, project and operation management, quality, sustainability, and entrepreneurship programs. In addition, partial least squares regression-structural equation modelling was used to analyze data. Based on the results, there is a significant impact of MOOC implementation factors on the continuance intention of students. Nevertheless, students showed a high intention to continue studying engineering in society courses online MOOC. Therefore, the current study provides practical evidence for management and lecturers of the university to enhance MOOC factors to ensure the high quality of teaching and enhance the continuance intention of students to study in a MOOC environment. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.